EXPLORING THE RELATIONSHIP AMONG IRAQI EFL TEACHERS’ MOTIVATION, AUTONOMY, SELF-EFFICACY, AND BURNOUT - Hasan Alzurfi, Assist Lect. Ali Falah; Sharrad , Assist Lect Ahmed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
This study attempted to examine the relationship between motivation, autonomy, self-Efficacy, and Burnout among Iraqi EFL instructor. 100 male and female instructors from different schools in Najaf, Iraq were invited to participate in the study. The participants were chosen through random sampling. The obtained data were analyzed using SPSS software. Three statistical tests that are not parametric (Pearson correlation) were applied to evaluate the obtained information. Results exhibited that Iraqi teachers' motivation and burnout mutually significant but negatively associated with each other. Furthermore, results showed that there existed a significant but negative correlation between Iraqi EFL lecturers' motivation and their burnout. Moreover, the results demonstrated that there was a meaningful but negative relationship between Iraqi EFL instructors' autonomy and their burnout. The findings suggest that identifying how different instructors are and how these variations catalyze varied performances among lecturers assist them to pass their difficulties effectively. Recognizing that an instructor who is powerful in one perspective is not necessarily powerful or weak in another perspective may also buttress how to aid teachers become better and to control their classes more effectively.